CONTRABAND CULTURES: reframing smuggling across latin america and the (Modern Americas Series, 2024)
Contraband Cultures presents narratives, representations, practices and imaginaries of smuggling and extra-legal or informal circulation practices, across and between the Latin American region (including the Caribbean) and its diasporas